Report of the Advisory Group on Consumer Industry Part I - Planning Commission (Planning Commission, 1989)
The Planning Commission constituted an Advisory Group on Consumer Industry in November 1985 under the chairmanship of Shri P.L. Tandon vide its office memorandum I&M-4(9)/21/85. In June 1986, in partial modification of the same memorandum, the Group was reconstituted under the chairmanship of Shri V.G. Rajadhyaksha, after Shri P.L. Tandon voluntarily resigned from the chairmanship.
Planning Commission
Planning Commission